2009
DOI: 10.1152/ajprenal.90609.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of sildenafil attenuates ischemia-reperfusion renal injury in rats

Abstract: Shin YT, Lee KW. Pretreatment of sildenafil attenuates ischemia-reperfusion renal injury in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 42 publications
(48 reference statements)
8
85
0
8
Order By: Relevance
“…Genetic mutations in parkin have been shown to be associated with familial PD (400). Although the role of parkin is still under investigation, it has been recently studied as a therapeutic for Parkinson's disease, as it is reportedly neuroprotective (1,102). UCH-L1 removes ubiquitin molecule from the Cterminal end of the poly ubiquitin polymer after attachment of the protein to the proteasome.…”
Section: Importance Of Clearance and Detoxification Systemsmentioning
confidence: 99%
“…Genetic mutations in parkin have been shown to be associated with familial PD (400). Although the role of parkin is still under investigation, it has been recently studied as a therapeutic for Parkinson's disease, as it is reportedly neuroprotective (1,102). UCH-L1 removes ubiquitin molecule from the Cterminal end of the poly ubiquitin polymer after attachment of the protein to the proteasome.…”
Section: Importance Of Clearance and Detoxification Systemsmentioning
confidence: 99%
“…Renal injury and failure following IR injury is ameliorated by the administration of Rho kinase inhibitors [6,8,10] and other drugs [11,12,13,14], and several mechanisms may be involved. We have shown that Rho kinase inhibition prevents a decrease in endothelium-dependent vasodilation and blood flow by enhancing endothelial nitric oxide synthase (eNOS) in resistance arteries thus antagonizing the downregulation induced by renal IR injury [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Renal function was evaluated as described previously [2]. Blood was collected from the inferior vena cava under anesthesia at sacrifice.…”
Section: Blood and Tissue Preparationmentioning
confidence: 99%
“…To measure blood urea nitrogen (BUN) and serum creatinine, aliquots of serum were analyzed using a chemistry auto-analyzer, Toshiba 200FR (Toshiba Medical Systems Co., Tokyo, Japan). Tissues were prepared as described previously [2]. Briefly, the left kidney was excised immediately after sacrifice and cut into three coronal sections.…”
Section: Blood and Tissue Preparationmentioning
confidence: 99%